Risk factors for incident peripheral arterial disease in type 2 diabetes: results from the Bypass Angioplasty Revascularization Investigation in type 2 Diabetes (BARI 2D) Trial - Althouse, Andrew D; Abbott, J Dawn; Forker, Alan D; Bertolet, Marnie; Barinas-Mitchell, Emma; Thurston, Rebecca C; Mulukutla, Suresh; Aboyans, Victor; Brooks, Maria Mori (Diabetes care, 2014)
The aim of this article was to define risk factors for incidence of peripheral arterial disease (PAD) in a large cohort of patients with type 2 diabetes mellitus (T2DM), overall and within the context of differing glycemic control strategies. The Bypass Angioplasty Revascularization Investigation in Type 2 Diabetes (BARI 2D) randomized controlled trial assigned participants to insulin-sensitizing (IS) therapy versus insulin-providing (IP) therapy. A total of 1,479 participants with normal ankle-brachial index (ABI) at study entry were eligible for analysis. PAD outcomes included new ABI ≤0.9 with decrease at least 0.1 from baseline, lower extremity revascularization, or lower extremity amputation. Baseline risk factors within the overall cohort and time-varying risk factors within each assigned glycemic control arm were assessed using Cox proportional hazards models. During an average 4.6 years of follow-up, 303 participants (20.5%) experienced an incident case of PAD. Age, sex, race, and baseline smoking status were all significantly associated with incident PAD in the BARI 2D cohort. Additional baseline risk factors included pulse pressure, HbA1c, and albumin-to-creatinine ratio (P < 0.05 for each). In stratified analyses of time-varying covariates, changes in BMI, LDL, HDL, systolic blood pressure, and pulse pressure were most predictive among IS patients, while change in HbA1c was most predictive among IP patients. Among patients with T2DM, traditional cardiovascular risk factors were the main predictors of incident PAD cases. Stratified analyses showed different risk factors were predictive for patients treated with IS medications versus those treated with IP medications.